PENGARUH eWOM (ELECTRONIC WORD OF MOUTH) DAN KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN MELALUI KEPUASAN SEBAGAI VARIABEL INTERVENING (STUDI PADA KONSUMEN SHOPEE KOTA SEMARANG) - Anastassya Rizkyta; Widayanto Widayanto; Naili Farida (Universitas Diponegoro, 2024)
Shopee is one of the online buying and selling sites that has made changes to be able to attract more customers to make transactions through the site. This study aims to determine the effect of electronic word of mouth and service quality on customer loyalty through Shopee customer satisfaction in Semarang City who have made transactions using the Shopee application. This type of research uses Explanatory research with a sample size of 100 respondents who are consumers of the shopee application. The sampling technique used Non Probability Sampling with purposive sampling method. This study uses Structural Equation Model data analysis techniques based on Partial Least Square (SEM PLS), which are estimated with the SmartPLS 4.0 for mac program. The results of data processing analysis with SmartPLS explain that electronic word of mouth, service quality and consumer loyalty have a positive and significant direct effect on satisfaction. Electronic word of mouth and consumer loyalty also have a positive and significant indirect effect on service quality, where together satisfaction has the greatest influence. The satisfaction variable in this study acts as a partial mediator. Recommendations are suggested for Shopee to first manage service quality, especially through the services provided to consumers. Keywords : Consumer Loyalty; Electronic Word of Mouth; Satisfaction; Service QualityShopee merupakan salah satu situs wadah jual beli melalui online yang telah melakukan perubahan untuk dapat menarik minat pelanggan agar lebih banyak yang melakukan transaksi melalui situs tersebut. Penelitian ini bertujuan untuk mengetahui pengaruh electronic word of mouth dan kualitas pelayanan terhadap loyalitas konsumen melalui kepuasan konsumen Shopee di Kota Semarang yang pernah melakukan transaksi menggunakan aplikasi Shopee. Tipe penelitian ini menggunakan Explanatory research dengan jumlah sampel sebanyak 100 responden yang merupakan konsumen aplikasi shopee. Teknik pengambilan sampel menggunakan Non Probability Sampling dengan metode purposive sampling. Penelitian ini menggunakan teknik analisis data Structural Equation Model berdasarkan Partial Least Square (SEM PLS), yang diestimasi dengan program SmartPLS 4.0 for mac. Hasil analisis olah data dengan SmartPLS menjelaskan bahwa electronic word of mouth, kualitas pelayanan dan loyalitas konsumen memiliki pengaruh langsung positif dan signifikan terhadap kepuasan. Electronic word of mouth dan loyalitas konsumen juga berpengaruh positif dan signifikan secara tidak langsung terhadap kualitas pelayanan, dimana ketika bersama-sama kepuasan memiliki pengaruh paling besar. Variabel kepuasan dalam penelitian ini berperan sebagai pemediasi parsial. Rekomendasi yang disarankan untuk pihak Shopee terlebih dahulu mengelola kualitas pelayanan terutama melalui pelayanan yang diberikan kepada konsumen. Shopee is one of the online buying and selling sites that has made changes to be able to attract more customers to make transactions through the site. This study aims to determine the effect of electronic word of mouth and service quality on customer loyalty through Shopee customer satisfaction in Semarang City who have made transactions using the Shopee application. This type of research uses Explanatory research with a sample size of 100 respondents who are consumers of the shopee application. The sampling technique used Non Probability Sampling with purposive sampling method. This study uses Structural Equation Model data analysis techniques based on Partial Least Square (SEM PLS), which are estimated with the SmartPLS 4.0 for mac program. The results of data processing analysis with SmartPLS explain that electronic word of mouth, service quality and consumer loyalty have a positive and significant direct effect on satisfaction. Electronic word of mouth and consumer loyalty also have a positive and significant indirect effect on service quality, where together satisfaction has the greatest influence. The satisfaction variable in this study acts as a partial mediator. Recommendations are suggested for Shopee to first manage service quality, especially through the services provided to consumers. Keywords : Consumer Loyalty; Electronic Word of Mouth; Satisfaction; Service Quality